2017
DOI: 10.1038/gt.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

AAV5-miHTT gene therapy demonstrates suppression of mutant huntingtin aggregation and neuronal dysfunction in a rat model of Huntington’s disease

Abstract: Huntington’s disease (HD) is a fatal progressive neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene. To date, there is no treatment to halt or reverse the course of HD. Lowering of either total or only the mutant HTT expression is expected to have therapeutic benefit. This can be achieved by engineered micro (mi)RNAs targeting HTT transcripts and delivered by an adeno-associated viral (AAV) vector. We have previously showed a miHTT construct to induce total HTT knock-down in Hu128/21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 43 publications
(54 reference statements)
2
68
0
Order By: Relevance
“…In addition, nonhuman primate studies have demonstrated that reductions in normal Htt of up to 45% may be well tolerated [60,61]. An engineered microRNA targeting human huntingtin, delivered via AAV5 with a transgene encoding an engineered miRNA against HTT mRNA (AAV5-miHTT), has been developed [62][63][64]. Widespread distribution of the transgene has been observed, as would be expected from the properties of AAV5 [5], and as would be desired for this disorder.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…In addition, nonhuman primate studies have demonstrated that reductions in normal Htt of up to 45% may be well tolerated [60,61]. An engineered microRNA targeting human huntingtin, delivered via AAV5 with a transgene encoding an engineered miRNA against HTT mRNA (AAV5-miHTT), has been developed [62][63][64]. Widespread distribution of the transgene has been observed, as would be expected from the properties of AAV5 [5], and as would be desired for this disorder.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Many of the symptoms observed in HD patients are highly related to the loss of MSNs in the striatum 6 and can be mimicked in rodent 7 , pig 8 , and non-human primate 9 models. Previous studies have achieved some success in HD animal models through cell transplantation [10][11][12] or using antisense oligonucleotides 13,14 and CRISPR/Cas9 gene editing technology 15 to reduce the mHtt level. Tetrabenazine has been used to treat chorea in HD and other movement disorders but with significant side effects 16 .…”
mentioning
confidence: 99%
“…70 Several studies reported inhibition of mutant HTT aggregate formation, and this reduced neuronal dysfunction in HD rats. 38,71,72 In a nonhuman primate study, AAV1-miRNA targeting rhesus HTT was MRI-guided stereotactically injected in the right and left putamen, which induced 45% HTT reduction in the mid and caudal putamen, without inducing neuronal degeneration, astrogliosis, or an immune response until termination of the study at 6 weeks. 37 Similarly, injections of AAV2-shRNA targeting rhesus HTT induced welltolerated 30% HTT reduction in the injected putamen measured at 6 months post injections.…”
Section: Long-term Htt Loweringmentioning
confidence: 99%
“…15 Those models are suitable for evaluating suppression of neurodegeneration, as indeed was demonstrated for different miRNAs and shRNAs that lower HTT. 71,72 The second HD rat model is transgenic, with a human HTT cDNA fragment containing 51 CAGs, whereas the expression is under control of the rat Htt promoter. 92 These rats manifest with adult-onset neurodegeneration and motor, cognitive, and behavioral deficits.…”
Section: Rodent Hd Modelsmentioning
confidence: 99%
See 1 more Smart Citation